2011
DOI: 10.1038/jid.2011.177
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptors as Therapeutic Targets in Human Melanoma: Synergism with BRAF Inhibition

Abstract: Cutaneous melanoma is a tumor with rising incidence and a very poor prognosis at the disseminated stage. Melanomas are characterized by frequent mutations in BRAF and also by overexpression of fibroblast growth factor 2 (FGF2), offering opportunities for therapeutic intervention. We investigated inhibition of FGF signaling and its combination with dacarbazine or BRAF inhibitors as an antitumor strategy in melanoma. The majority of melanoma cell lines displayed overexpression of FGF2 but also FGF5 and FGF18 tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 42 publications
5
73
0
1
Order By: Relevance
“…Moreover, treatment with recombinant PTX3 protein similarly affected cell proliferation and EMT in BRAFmutated human A375 and A2058 melanoma cells. In keeping with these observations, blockade of FGF signals by dominant-negative receptors or tyrosine kinase inhibitors reduces melanoma growth and synergistically enhances the antimelanoma effect of BRAF inhibition (16).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Moreover, treatment with recombinant PTX3 protein similarly affected cell proliferation and EMT in BRAFmutated human A375 and A2058 melanoma cells. In keeping with these observations, blockade of FGF signals by dominant-negative receptors or tyrosine kinase inhibitors reduces melanoma growth and synergistically enhances the antimelanoma effect of BRAF inhibition (16).…”
Section: Discussionmentioning
confidence: 75%
“…A preliminary analysis has revealed that, besides FGF2, PTX3 efficiently binds FGF8b, FGF17, and with a lower affinity FGF6 and FGF10 (22). Deregulation of the FGF/ FGFR system in melanoma may occur by overexpression of FGF2 and to a lesser extent of FGF5 and FGF18 (16). FGFR1 overexpression (14) and activating FGFR1 gene mutation (49) have been also reported in melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antitumor effect of FGFR inhibitors (SU5402 and PD166866) in combination with BRAF inhibitors was shown in vitro and in vivo in a set of BRAF mutant melanoma cells [51]. The small molecule multitarget kinase inhibitor BIBF-1120 acting on FGF, VEGF and PDGF receptors inhibited the proliferation of a large panel of tumor cells including kidney, pharyngeal, ovary, lung, colon, pancreatic cancer and glioma cells in vitro and antitumor effect in vivo [52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…122 FGF2 is overexpressed on melanoma cells, but not on normal melanocytes, 123 and has been linked to tumor progression in multiple malignancies, including melanoma.…”
Section: Perspectivementioning
confidence: 99%